An investigation into the influence of superdisintegrant type on properties of liquisolid systems with different carriers - Glišić, Teodora; Vasiljević, Ivana; Parojčić, Jelena; Aleksić, Ivana (Archives of Pharmacy, 2022)
Tablet disintegration in gastrointestinal fluids and the resulting increase in surface area available for drug dissolution is one of the preconditions for achieving acceptable bioavailability. Disintegrant addition shortens the disintegration time, but it can also affect flowability and mechanical properties of liquisolid systems. The aim of this study was to examine the influence of superdisintegrant type and concentration on flowability, tensile strength and disintegration time of liquisolid systems prepared using three different carriers. The admixtures were prepared in a fluid bed processor. Syloid® XDP3050, Neusilin® US2 and Fujicalin® were used as carriers, with liquid phase (macrogol 400) content of 40.4%, 54.8% and 14.8%, respectively, and carrier to coating material (colloidal silicon dioxide) ratio R=30. Superdisintegrant (croscarmellose sodium, crospovidone, sodium starch glycolate) concentration ranged from 2 to 5%. Admixtures’ flowability and compacts’ tensile strength and disintegration time were determined. Admixtures with Fujicalin® showed the best flowability. Superdisintegrant addition decreased flowability, except for Syloid® XDP3050 admixtures where flowability improved with increase in disintegrant concentration. Sodium starch glycolate had the most pronounced influence on the compact tensile strength. Regardless of the carrier used, the increase in its concentration led to decrease in tensile strength. Notable differences in the disintegration time were observed, depending on the type of carrier and superdisintegrant. Compacts with Fujicalin® disintegrated within the required time without the superdisintegrant addition. The shortest disintegration time, for compacts with Syloid® XDP3050 and Neusilin® US2, as well as the highest tensile strength, for compacts with Syloid® XDP3050, were achieved with croscarmellose sodium.